The importance of monitoring in remote teaching: Experiences of a nursing student in the collaborative teaching-learning process in academic training - Morais, Breno Alves de; Salha, Daniella Regina Arantes Martins; Blaha, Carlos Alfredo Galindo (Seven Editora, 2023)
This is an experience report of a quantitative descriptive approach about the performance of the Monitor’s Integrated Monitoring project of the Department of Cell Biology and Genetics (MIC-DBG) of UFRN during Emergency Remote Teaching in the pandemic caused by SARS CoV-2. The Monitoring actions were developed with Ecology, Nursing, Dentistry and Pharmacy students, assisting the teachers of 03 classes of Cellular and Molecular Biology and 01 class of Genetics, making a population of 102 students. The use of TDICs in synchronous and asynchronous actions was of relevant importance for both students and professors, and none of them had sufficient skills and competencies to face higher education in the ERE condition as a strategy for continuing the general activities of the global population. The limitations and restrictions were not the same for the actors of the teacher-student teaching process and, consequently, for the Monitor. The results of the Monitor’s actions were successful both with Cellular and Molecular Biology classes and with the Genetics class, where the use of Instagram and Whatsapp was the main communication link. The actions included group discussions, holding scavenger hunts through Instagram, providing didactic material, solving exercises discussed remotely, and also using virtual laboratories, online simulators, animations and games of biocellular processes, culminating with the unique opportunity that Monitoring provides, that of teaching a theoretical class supervised by the teacher. There was good adherence of the students with participation in the discussions and search for monitoring to remove doubts individually with preferential use of messaging applications (insert the numbers %). Reports from the students in the groups (67%) point to TDICs as great strategies for a greater assimilation of the content, as well as an improvement in the performance of the evaluations due to the contribution of the monitor. In this report of the experiences of a Bachelor’s Degree in Nursing student as an Integrated Monitor, it is noted that, although the challenges experienced during the pandemic have affected the population in several instances, and in education it was no different, the possibilities with new technologies in line with synchronous and asynchronous remote teaching, it was possible to reap good results during the Emergency Remote Teaching (ERE), which contributed so much to the maturation and strengthening of the student triad - Integrated Monitor – Teacher. DOI:https://doi.org/10.56238/innovhealthknow-050